Perjuangan dalam Ketidakpastian”: Studi Etnografi Usaha Bisnis Rintisan/Start-Up oleh Anak Muda di D.I. Yogyakarta - Arif Budi Darmawan; Azinuddin Ikram Hakim; Yuni Afita Sari (Jurnal Studi Pemuda, 2020)
From previous generation’s point of view, building a start-up business is still frequently considered as a devi- ated choice because of its inherent risk. However, instead of avoiding it, some ordinary youth category prefer to choose to plunge in the risk itself. This article applies participation observation and in-depth interview as data collection technique. By the process, the result is that start-up business becomes a form of the subculture careers based on ordinary youth category, in which this business is subjectively as a symbol to express their language of restlessness and resistance through development of passion differently from dominant culture.